Yarns about bush characters in the Alex Hood collection of folkloric recordings - Marshall, Jack.; Harney, Bill, 1931-; Moore, Gerald, 1899-1987.; Hood, Alex, 1935- (1974)
Folkloric recording. A.B.C. sessions with Jack Marshall and Bill Harney, yarn swapping about bush characters. Farewell from Gerald Moore.
SIDE 1, tells stories about: 'Speewah' -- 'Gentle Annie' -- Aboriginal story styles -- Aboriginal idiom verses -- Didgeridoo rhythms -- Pidgin story -- 'Black Andy' tales -- tales of big swags -- murder story -- Sleeper cutter story -- centipede story -- Gecko yarn -- story of pump -- damper making -- playing buton accordion and dance music. SIDE 2: Performances by various classical singers, Gerald Moore playing the piano.
Recorded in 1974.
Digital master available
Summary (1 p.)
Keywords: Folklore -- Australia; Tales -- Australia